Tindak Pidana Pelaku Penyebaran Konten Pornografi Terhadap Anak Dibawah Umur - Komang Wiraguna; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2020)
Abstract—The child becomes part of the successor Nations largely determine the fate of the whole nation in the future; all children in the world have the right to obtain the right to continue to evolve. Within the community often encountered that child becomes the perpetrator of a criminal offence the dissemination of Pornographic Content that is a legal issue that concerns about a picture, photo, video, illustrations, sketches, containing about lewd action according to Law Number 44 the year 2008. Children who are bound in criminal cases will be processed for criminal justice in adili special children in accordance with the Law Number 11 of the year 2012. Children who have committed criminal acts will be given legal protection. The purpose of this research in order to find out how legal consequences for a child who spread pornographic content as well as the consideration of judges in meting out the verdict. The writing is pendektan because it uses the normative legislation and comparative law. In the trial the judge defending children is a children's judge.